\(11.5^{2n}+2^{3n+2}+2^{3n+1}\)
\(=17.5^{2n}-6.5^{2n}+2^{3n}.6\)
\(=17.5^{2n}-6\left(5^{2n}-2^{3n}\right)\)
\(=17.5^{2n}-6\left(25^n-8^n\right)\)
Có \(17.5^{2n}⋮17\)
\(25^n-18^n⋮\left(25-18\right)⋮17\left(với\forall n\right)\)
\(\RightarrowĐpcm\)
11.52n + 23n+2 + 23n+1
= 11.25n + 4.23n + 2.23n
= 17.25n - 6.25n + 2.23n.(2+1)
= 17.25n - 6.25n + 6.23n
= 17.25n - 6.(25n - 23n)
= 17.25n - 6.(25n - 8n)
mà 25 - 8 = 17 chia hết cho 17
=> 25n - 8n chia hết cho 17
=> 17.25n - 6.(25n - 8n) chia hết cho 17
=> đpcm